Strategy of the National Narcotics Agency of North Sumatera in Effort to Prevent Drug Abuse in Medan City - Abfandi, Hanafi; Ginting, Wiro Oktavius (International Journal Administration, Business & Organization, 2025)
Drug abuse and distribution remain critical challenges in Indonesia, with Medan City experiencing notably high case rates. This research responds to the growing urgency for effective governmental intervention. The study explores the implementation of preventive strategies by the National Narcotics Agency of North Sumatra in addressing drug abuse in Medan. Using a qualitative research design, data were collected over three months through observation, document analysis, and interviews with five purposively selected respondents. The study employs the strategic implementation framework of Hunger and Wheelen, focusing on program, budget, and procedural indicators. Results show that the agency has initiated various preventive measures, including awareness campaigns, counseling sessions, urine testing, technical training, and the development of drug-free sub-districts. Budget planning is managed effectively, with national funds allocated through detailed operational plans, while procedures are followed consistently to ensure structured program execution. Additionally, the reach of these initiatives remains suboptimal, primarily due to resource constraints. This study contributes to the literature by applying a managerial strategy lens to public drug prevention. The study underscores the necessity to increase resources, expand personnel, and establish a dedicated National Narcotics Agency office in Medan to enhance future prevention efforts.